Analisis Risiko Pengadaan Tanah Untuk Eksplorasi dan Eksploitasi Minyak dan Gas Bumi (Studi Kasus : PT.Pertamina EP- Paku Gajah Development Project) - Presetyo Firgianto; Prof. Dr. S. Pantja Djati, M.Si., MA (Pasca Sarjana UKI, 2020)
Upstream oil and gas activities both searching up to oil and gas production are government programs where activities are regulated in legislation. Before drilling, to obtain oil and gas reserves, the need for land for drilling activities is a step that must be passed. Since the upstream oil and gas activities are government programs, the government guarantees the availability of land for such activities that can be classified into the public interest and set forth in Law No. 2 of 2012 on Land Procurement for Development for the Public Interest. The formulation of the problem in this research is : How the stages of activities Land acquisition for the public interest PT.Pertamina EP - Paku Gajah Development Project?, What are the opportunities and impacts at each stage of the activity ? Land acquisition for public interest PT.Pertamina EP - Paku Gajah Development Project ?, and How is the mitigation effect of each stage of Land Acquisition activities for This research uses semi-quantitative descriptive method. The data collection tool used is questionnaire with liekert scale (1-5). The results of this study indicate that the stages of land acquisition for the public interest consists of planning, preparation, implementation, and delivery of results.